Management of hazardous solid waste during the hydrocarbon spill in Ventanilla - Huiman Cruz, Alberto (2023)
The investigation constitutes an analysis of the management of hazardous solid waste during the hydrocarbon spill in Ventanilla. The method used is descriptive and comparative, consisting of the search, evaluation and analysis of the facts. Inadequate waste management was evidenced during the hydrocarbon clean-up work. After the accident occurred, the quantity and physical composition of the waste generated were not strictly accounted for, a waste hierarchy must be defined due to its dangerousness, prioritizing the separation of waste at the source of generation, and the prevention of secondary pollution. Contingency planning must incorporate handling and storage at the source: temporary storage with impermeable containers, transport through clearly defined and signposted accesses, and define final disposal in secure landfills. It is concluded that hazardous solid waste is the responsibility of the generator, under the principle of Internalization of Costs and Polluter-Payer. Waste management was inadequate due to lack of infrastructure and equipment little concurrent support from the State, limited staff training; and lack of multisectoral work with defined roles and functions. The effects caused were informal activities that put the recovery of the ecosystem at risk and limited the opportunity to take positive lessons.